Pengaruh Return On Equity dan Leverage Pada Saham Bonus di Perusaaan yang Terdaftar di Bursa Efek Indonesia - Rai Sukmawati Dana; Komang Ayu Krisnadewi (InFestasi, 2017)
This study aimed to determine the effect of return on equity (ROE) and leverage of the bonus shares in companies listed on the Stock Exchange in 2000-2015. The total samples that used ware 33 observations based on saturated samples method. The analysis technique used multiple linear regression analysis. The results showed ROE does not had an effect on bonus shares that means the company's decision to publish bonus shares does not depend on the size of ROE, leverage had a positive effect on bonus shares that shows if the company’s risk increased, so the possibility of the company to publish bonus shares will higher than cash dividends in the future.